Chemical fate and transport in the environment - Hemond, Harold F. (Academic Press, 2000)
"This newly updated and expanded edition of Chemical Fate and Transport in the Environment covers the fundamental principles of mass transport, chemical partitioning, and chemical/biological transformation in surface waters, in soil and groundwater, and in air. In this textbook, each of these three major environmental media is introduced by descriptive overviews, followed by presentation of the controlling physical, chemical, and biological processes. Emphasis is placed on intuitively based mathematical models for chemical transport and transformations. Although developed for a one-semester graduate course, Chemical Fate and Transport in the Environment, Second Edition, is also an essential reference for environmental practitioners in industry, consulting, and government agencies."--Jacket